2013
DOI: 10.1177/0300985813476055
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Cattle With Cryptosporidium parvum

Abstract: Mast cells might play an important role as the major effector cells in the immune response against Cryptosporidium parvum. C. parvum is a protozoan parasite that causes cryptosporidiosis in animals and humans worldwide. To investigate the interaction between C. parvum and mast cells during infection, nine 3-day-old male calves were orally challenged with 10 6 oocysts of C. parvum per calf. The distribution of mast cells in the mucosa of the small intestine was analyzed by toluidine blue staining. The concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…In the present study, IFNc, IL-12 and IL-14 in the supernatants of infected nontreated groups were more than those of the control noninfected ones. Our results suggested that the C. parvum infection induced a Th1 response, a finding that agreed with Li et al (2013). Also, our results agreed with Marchi et al (2014) who reported that IL-12 and IFN-c promoted development of naïve CD4?…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, IFNc, IL-12 and IL-14 in the supernatants of infected nontreated groups were more than those of the control noninfected ones. Our results suggested that the C. parvum infection induced a Th1 response, a finding that agreed with Li et al (2013). Also, our results agreed with Marchi et al (2014) who reported that IL-12 and IFN-c promoted development of naïve CD4?…”
Section: Discussionsupporting
confidence: 91%
“…The early immune response of neonatal ruminants to C. parvum infection is still largely unknown although some insight has been gained on the recruitment of CD8 lymphocytes by Wyatt et al [10,52] and of mast cells by Li et al [53] in the gut of infected calves. Natural Killer (NK) cells have been known for a long time to be important actors of the primary innate immune response through cytotoxicity and IFNγ production and also through a regulatory role in the immune response via their interaction with other cells and their ability to produce various cytokines once activated.…”
Section: Discussionmentioning
confidence: 99%